Rationality of the Choice of Profession as the Psycho-Educational Problem - Petrauskaitė, Ramutė (Acta Paedagogica Vilnensia, 1993)
The article maintains that a rational choice of profession takes place when the personality is aware of major own characteristics and features of chosen vocation, their levels of matching, and foresees the future prospects of professional activity. In order to identify the level of rationality of the choice of profession in schoolchildren (candidates to philology at Klaipeda University) Fukuyama test (abbreviated as F-test) was applied. This test has been adapted in the design of research methodology: in view of the prevailing practice in Lithuanian schools part 4 of the F-test had been changed. This methodology was applied in interviewing 60 pupils and their teachers. The study partially confirmed the hypothesis that the level of professional rationality of the future philology students should be high. However, about a quarter of the students surveyed showed significant deviations from the general level. It was also noted that teachers tended to evaluate the personal characteristics of the students higher than the students themselves. However, applied methodology did not allow for the explanation of the causes of this phenomenon.